Employability Model Reviewed from Career Planning, Self-Adjustment, and Need for Achievement - Alya Surya Diningrum; Fatwa Tentama (Psyche 165 Journal, 2025)
Vocational High Schools play a crucial role in preparing graduates to enter the workforce. However, many Vocational High School graduates continue to face challenges in achieving optimal work readiness. These issues highlight the need for further research to identify the factors that influence students’ employability. This study aims to test a theoretical model examining the influence of career planning, self-adjustment, and need for achievement on the employability of Vocational High School students. The research employs a quantitative approach, utilizing Structural Equation Modeling (SEM) for data analysis. The participants comprised 360 Grade XII students from Vocational High School "X", selected through a cluster random sampling technique. Data were collected using standardized scales that measured employability, career planning, self-adjustment, and the need for achievement. The analysis was conducted using SEM-PLS with the SmartPLS software, version 4.1.1.1. The results indicate that the proposed model—where employability is influenced by career planning, self-adjustment, and need for achievement—demonstrates a good fit with the empirical data. Further analysis reveals a highly significant positive effect of career planning on employability, as well as significant positive effects of both self-adjustment and need for achievement on employability. Based on these findings, the study concluded that the model is valid and applicable for explaining the factors that influence the employability of vocational high school students. The results support the importance of fostering career planning, adaptability, and achievement motivation to enhance students' readiness for the workforce.